ON THE ISSUE OF INNOVATIVE ACTIVITY STIMULATION MANAGEMENT ON SOME OIL-PROCESSING ENTERPRISES OF RUSSIAN FEDERATION - T. R. Karimov (Russian Journal of Economics and Law)
The article views the topical issues of managerial process in innovative activity stimulation by example of three oil-processing plants of the Russian Federation - "TAIF-NK" Public Corporation, "Ufimskiy NPZ" Public Corporation and "Moskovskiy NPZ" Public Corporation. The author gives statistical data, analytical argument, comments and conclusions on the essential similarities and differences in the process under study. The measures necessary for its modernization are listed.